2022
DOI: 10.1021/acs.jpca.2c06314
|View full text |Cite
|
Sign up to set email alerts
|

Energy Transfer and Restructuring in Amorphous Solid Water upon Consecutive Irradiation

Abstract: Interstellar and cometary ices play an important role in the formation of planetary systems around young stars. Their main constituent is amorphous solid water (ASW). Although ASW is widely studied, vibrational energy dissipation and structural changes due to vibrational excitation are less well understood. The hydrogen-bonding network is likely a crucial component in this.Here, we present experimental results on hydrogen-bonding changes in ASW induced by the intense, nearly monochromatic mid-IR free-electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…Fredon et al (2021) have explored the dissipation of different types of energy (i.e., vibrational, rotational and translational) by admolecules on top of an ASW surface using molecular dynamics simulations. They observed that the distribution of vibrational energy among the species' vibrational modes heavily impacts the energy dissipation channels, in agreement with our experimental results and those of previous IR-FEL exposure works (Noble et al 2020;Ioppolo et al 2022;Coussan et al 2022;Cuppen et al 2022). They also concluded that the dissipation of vibrational energy from the admolecule to the surface occurs through the excitation of a surface-admolecule bond, and therefore intermolecular interactions play a key role in this processwhich is corroborated by our experimental results.…”
Section: Morphologysupporting
confidence: 92%
“…Fredon et al (2021) have explored the dissipation of different types of energy (i.e., vibrational, rotational and translational) by admolecules on top of an ASW surface using molecular dynamics simulations. They observed that the distribution of vibrational energy among the species' vibrational modes heavily impacts the energy dissipation channels, in agreement with our experimental results and those of previous IR-FEL exposure works (Noble et al 2020;Ioppolo et al 2022;Coussan et al 2022;Cuppen et al 2022). They also concluded that the dissipation of vibrational energy from the admolecule to the surface occurs through the excitation of a surface-admolecule bond, and therefore intermolecular interactions play a key role in this processwhich is corroborated by our experimental results.…”
Section: Morphologysupporting
confidence: 92%
“…Furthermore, despite both ices containing the same column density of CO molecules, the higher abundance of surrounding CH 3 OH species in the methanol-rich ice results in more intense changes to the CO band, even upon irradiation at 4.67 µm. As was observed by Cuppen et al (2022) in H 2 O ices, it is likely that the higher fraction of hydrogen-bonded species in the CH 3 OH-rich mixture facilitates the vibrational energy transfer in comparison to the CO-rich counterpart, thus resulting in more intense spectral changes. In both ice mixtures, irradiations at the CHstretching bands of methanol (not shown) yield similar changes to the other modes, but less intense.…”
Section: Morphologymentioning
confidence: 62%
“…Alternatively, this difference could also be related to the type of intermolecular interactions within the ice, in which H-bonding networks could potentially facilitate the vibrational energy dissipation through restructuring, while generally weaker van der Waals interactions could be less efficient in doing so. Indeed, transfer of vibrational energy has been shown to occur in H 2 O ices through hydrogen-bonded water molecules with resonant O-H stretches, which leads to local heating and restructuring of the ice (Cuppen et al 2022).…”
Section: Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigations of the effect of selective infrared irradiation of water ice have shown that desorption 40,41 and restructuring 42,43 of the water ice can take place, with the exact effects depending on which vibrational modes of the water are excited. A more recent study of the infrared free-electron laser irradiation of CO 2 ice 44 under astrophysically relevant conditions has also shown that restructuring of the ice, as well as photodesorption, occurs following irradiation with infrared light.…”
Section: Introductionmentioning
confidence: 99%